A rare case of herniation of liver through incision of cabg: A case report and review of literature - Ansari, Sharique; Shaikh, Tanveer Parvez; Mandhane, Nisha; Deolekar, Sandesh; Karandikar, Sangram (International Journal of Research in Medical Sciences, 2017)
Herniation of liver through an incision of previous surgery is a very rare phenomena. Here we present a case of herniation of part of left lobe of liver through a defect in the anterior abdominal wall due to previous coronary artery bypass surgery (CABG) surgery. Up till now only two cases have been reported for liver herniation through scar of previous of CABG surgery and this would be the third case as per our knowledge.